The faces of Margraten
1 online resource
Keywords: In the rolling hills of the Limburg Province, near the village of Margraten, they slowly loom up, row after row: thousands of white marble crosses and Stars of David. They mark the final resting place of American soldiers who died fighting to liberate the Netherlands during World War II. While the headstones provide the names and ages of those lost, they cannot tell us who these soldiers were, what their lives were like, or who they left behind. Nor can the peace and quiet at the only American military cemetery in the Netherlands reflect the harrowing experience and violent final moments of the men and women who forever rest here. Through hundreds of personal photographs and more than 250 stories, The Faces of Margraten gives these soldiers faces and voices again, telling not only the history of World War II and the ending of the German occupation of the Netherlands, but also revealing how and why the Dutch people have never forgotten their liberators. Concluding with a list of all the soldiers' names, this commemorative book stands as a testament to the service and sacrifice of the more than 10,000 Americans buried or memorialized as missing in Margraten.